Impaired heme binding and aggregation of mutant cystathionine beta-synthase subunits in homocystinuria - Janosík, M; Oliveriusová, J; Janosíková, B; Sokolová, J; Kraus, E; Kraus, J P; Kozich, V (American journal of human genetics, 2001)
During the past 20 years, cystathionine beta-synthase (CBS) deficiency has been detected in the former Czechoslovakia with a calculated frequency of 1:349,000. The clinical manifestation was typical of homocystinuria, and about half of the 21 patients were not responsive to pyridoxine. Twelve distinct mutations were detected in 30 independent homocystinuric alleles. One half of the alleles carried either the c.833 T-->C or the IVS11-2A-->C mutation; the remaining alleles contained private mutations. The abundance of five mutant mRNAs with premature stop codons was analyzed by PCR-RFLP. Two mRNAs, c.828_931ins104 (IVS7+1G-->A) and c.1226 G-->A, were severely reduced in the cytoplasm as a result of nonsense-mediated decay. In contrast, the other three mRNAs-c.19_20insC, c.28_29delG, and c.210_235del26 (IVS1-1G-->C)-were stable. Native western blot analysis of 14 mutant fibroblast lines showed a paucity of CBS antigen, which was detectable only in aggregates. Five mutations-A114V (c.341C-->T), A155T (c.463G-->A), E176K (c.526G-->A), I278T (c.833T-->C), and W409_G453del (IVS11-2A-->C)-were expressed in Escherichia coli. All five mutant proteins formed substantially more aggregates than did the wild-type CBS, and no aggregates contained heme. These data suggest that abnormal folding, impaired heme binding, and aggregation of mutant CBS polypeptides may be common pathogenic mechanisms in CBS deficiency.
Keywords: Protein Binding; Mutation, Missense; RNA, Messenger; cystathionin-beta-synthasa; Codon, Terminator; fibroblasty; hem; mutace; Cystathionine beta-Synthase; missense mutace; Male; Middle Aged; Fibroblasts; Genotype; nesmyslný kodon; Adolescent; western blotting; Child; dítě; molekulární sekvence - údaje; Adult; dospělí; mužské pohlaví; Protein Subunits; messenger RNA; podjednotky proteinů; mladiství; vazba proteinů; Blotting, Western; lidé; ženské pohlaví; Humans; terminační kodon; Codon, Nonsense; polymorfismus délky restrikčních fragmentů; genotyp; Molecular Sequence Data; Heme; Mutation; Alleles; Female; alely; lidé středního věku; homocystinurie; Polymorphism, Restriction Fragment Length; Homocystinuria